The Effectiveness of Self-Care Enhancement Based Intervention Among Type 2 Diabetes Mellitus: A Systematic Review - Yusron Amin; Haswita Haswita (International Journal of Advanced Health Science and Technology, 2026)
Poor glycemic control and the high prevalence of complications among individuals with type 2 diabetes mellitus (T2DM) remain major public health challenges and are strongly associated with inadequate self-care behaviors. Despite the growing implementation of self-care–based interventions, evidence regarding their effectiveness on glycemic outcomes and self-care activities remains inconsistent. This systematic review aimed to evaluate the effectiveness of self-care enhancement–based interventions in improving glycemic control and self-care behaviors among adults with T2DM. A systematic search was conducted across four electronic databases PubMed, ScienceDirect, ProQuest, and Google Scholar using relevant keywords related to self-care, intervention, and T2DM. Studies published between 2019 and 2024, written in English, available in full text, and employing randomized controlled trial or quasi-experimental designs were included. Article selection followed the PRISMA framework, and methodological quality was assessed using the Joanna Briggs Institute (JBI) critical appraisal tools. Eight eligible studies were included in the final synthesis. The findings demonstrated heterogeneous outcomes across interventions. Most studies (n = 5) reported significant reductions in HbA1c levels accompanied by improvements in self-care activities, including diet management, blood glucose monitoring, and self-efficacy. One study showed a significant reduction in HbA1c without corresponding improvements in self-care behavior, while two studies reported improvements in self-care activities without significant changes in HbA1c. Interventions that incorporated structured, personalized education and ongoing monitoring, supported by family or community involvement, consistently yielded more favorable outcomes. In conclusion, self-care enhancement–based interventions are generally effective in improving glycemic control and self-care behaviors among individuals with T2DM, particularly when delivered through a structured, person-centered approach integrated with social support systems. These findings highlight the importance of comprehensive and context-sensitive intervention designs in diabetes self-management programs.